2014
DOI: 10.1063/1.4873881
|View full text |Cite
|
Sign up to set email alerts
|

Selective light sintering of Aerosol-Jet printed silver nanoparticle inks on polymer substrates

Abstract: Printing silver nanoparticle inks to generate conductive structures for electronics on polymer substrates has gained increasing relevance in recent years. In this context, the Aerosol-Jet Technology is well suited to print silver ink on 3D-Molded Interconnect Devices (MID). The deposited ink requires thermal post-treatment to obtain sufficient electrical conductivity and adhesion. However, commonly used oven sintering cannot be applied for many thermoplastic substrates due to low melting temperatures. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The thermal sintering before the photonic curing was performed for removing the solvent from the printed structure. Performing the photonic curing of printed structures with high solvent content can lead to an explosive evaporation of the solvent and cause damage of the printed structures [36].…”
Section: Discussionmentioning
confidence: 99%
“…The thermal sintering before the photonic curing was performed for removing the solvent from the printed structure. Performing the photonic curing of printed structures with high solvent content can lead to an explosive evaporation of the solvent and cause damage of the printed structures [36].…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to oven and CO 2 -laser thermal treatment, light-induced sintering has also been discussed as an approach to postcure nanoparticle-based inks on polymer substrates. 389 In this case, the sintering step takes advantage of the specific absorption related to the nanoparticles’ plasmonic resonance, thereby enabling localized heating and sintering of the metallic ink while only marginally heating the substrate.…”
Section: Materials and Binder Jettingmentioning
confidence: 99%
“…common thermoplastics), Hoerber et al [53] showed that non-sintered deposits with larger interconnect dimensions can be used, while Werner et al [51] presented electrical sintering as an alternative for thermally sensitive substrates. In later work, Schuetz et al [54] The use of nanoparticle inks presents serious limitations for the application of AJP interconnects. The high surface area-tovolume ratio of metallic nanoparticles makes them highly susceptible to loss of conductivity through oxidation.…”
Section: Interconnectsmentioning
confidence: 99%